Latitudinal trends in the structure, similarity and beta diversity of plant communities invaded by Alternanthera philoxeroides in heterogeneous habitats - Wu, Hao; Dong, Sijin; Rao, Benqiang (Frontiers in Plant Science, 2022)
Variations in latitudinal gradients could lead to changes in the performance and ecological effects of invasive plants and thus may affect the species composition, distribution and interspecific substitution of native plant communities. However, variations in structure, similarity and beta (β) diversity within invaded communities across latitudinal gradients in heterogeneous habitats remain unclear. In this study, we conducted a two-year field survey along 21°N to 37°N in China, to examine the differential effects of the amphibious invasive plant Alternanthera philoxeroides on native plant communities in terrestrial and aquatic habitats. We compared the differences in the invasion importance value (IV), species distribution, community similarity (Jaccard index and Sorenson index) and β diversity (Bray‒Curtis index and βsim index) between terrestrial and aquatic communities invaded by A. philoxeroides, as well as analyzed their latitudinal trends. We found that the IV of A. philoxeroides and β diversity in aquatic habitats were all significantly higher than that of terrestrial, while the terrestrial habitat had a higher community similarity values. The aquatic A. philoxeroides IV increased with increasing latitude, while the terrestrial IV had no significant latitudinal trend. With increasing latitude, the component proportion of cold- and drought-tolerant species in the terrestrial communities increased, and the dominant accompanying species in the aquatic communities gradually changed from hygrophytes and floating plants to emerged and submerged plants. In addition, the aquatic communities had lower community similarity values and higher β diversity in higher latitudinal regions, while terrestrial communities had the opposite parameters in these regions. Our study indicates that the bioresistance capacities of the native communities to invasive A. philoxeroides in heterogeneous habitats are different; A. philoxeroides invasion leads to higher community homogenization in terrestrial habitats than in aquatic habitats, and terrestrial communities experience more severe homogenization in higher latitudinal regions. These findings are crucial for predicting the dynamics of invasive plant communities under rapid global change.